(untitled) (Revista de Investigaciones Universidad del Quindío, 2015)
Cerebrovascular and cardiovascular diseases are the leading cause of death in people over forty-fi ve years in the world. Recently, these conditions are also found in young people. These are chronic and non-communicable illnesses that are mainly related with modifi able risk factors inherent to lifestyles. However, there is a hereditary component that can be associated with the disease onset. This quantitative and descriptive study aimed to measure the prevalence of cerebrovascular and cardiovascular diseases risk factors that have been traditionally considered in the literature. Age, gender, ethnicity and family history were measured as non-modifiable risk factors. On the other hand, high alcohol consumption, cigarette smoking, physical inactivity, high body mass index and casual high blood pressure measurement, were assessed as modifi able risk factors. The most prevalent modifi able risk factors that were identifi ed in the group of young people between fi fteen and twenty fi ve years old were physical inactivity (87,8%) and high alcohol consumption (46,3%). Students with family history of cerebrovascular and cardiovascular diseases, with personal history of high blood pressure and diabetes mellitus were also recognized. As an emerging fi nding of the study, it was identifi ed that 6,5% of the student population was underweight (BMI <18) Data were compared with some similar national and international researches, fi nding modifi able risk factors with higher prevalence than the ones reported in our investigation.